Diagnostic challenges in the assessment of thyroid neoplasms using nuclear features and vascular and capsular invasion: a multi-center interobserver agreement study - Agnes Stephanie Harahap; Mutiah Mutmainnah; Maria Francisca Ham; Dina Khoirunnisa; Abdillah Hasbi Assadyk; Husni Cangara; Aswiyanti Asri; Diah Prabawati Retnani; Fairuz Quzwain; Hasrayati Agustina; Hermawan Istiadi; Indri Windarti; et al. (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
Background The diagnosis of thyroid neoplasms necessitates the identification of distinct histological features. Various education/hospital centers located in cities across Indonesia likely result in discordances among pathologists when diagnosing thyroid neoplasms. Methods This study examined the concordance among Indonesian pathologists in assessing nuclear features and capsular and vascular invasion of thyroid tumors. Fifteen pathologists from different centers independently assessed the same 14 digital slides of thyroid tumor specimens. All the specimens were thyroid neoplasms with known BRAFV600E and RAS mutational status, from a single center. We evaluated the pre- and post-training agreement using the Fleiss kappa. The significance of the training was evaluated using a paired T-test. Results Baseline agreement on nuclear features was slight to fair based on a 3-point scoring system (k = 0.14 to 0.28) and poor to fair based on an eight-point system (k = -0.02 to 0.24). Agreements on vascular (κ = 0.35) and capsular invasion (κ = 0.27) were fair, whereas the estimated molecular type showed substantial agreement (κ = 0.74). Following the training, agreement using the eight-point system significantly improved (p = 0.001). Conclusions The level of concordance among Indonesian pathologists in diagnosing thyroid neoplasm was relatively poor. Consensus in pathology assessment requires ongoing collaboration and education to refine diagnostic criteria.